A prospective, randomized, double-blind trial to compare body weight-adjusted and fixed doses of palonosetron for preventing postoperative nausea and vomiting in obese female patients. - Nathalia Gouveia de Araujo Ferreira; Ismar Lima Cavalcanti; Alexandra Rezende Assad; Louis Barrucand; Estêvão Luiz Carvalho Braga; Nubia Verçosa (PLoS ONE)
Background Postoperative nausea and vomiting (PONV) is a common postsurgical complication. Palonosetron is effective for PONV prevention at the usual dose of 75 μg, but the ideal dose for obese patients has not yet been investigated. The aim of this study was to compare body weight-adjusted and fixed doses of palonosetron for preventing PONV in obese female patients. Materials and methods We performed a prospective, randomized, double-blind trial involving 80 female patients, aged 18-80 years with an American Society of Anesthesiologists physical status of 2 and 3 and a body mass index (BMI) ≥ 30 kg m-2 who were scheduled to undergo elective breast surgery. Patients received an intravenous body weight-adjusted dose of palonosetron (1 μg kg -1, GI = 40 patients) or a fixed dose of palonosetron (75 μg, GII = 40 patients). All patients received dexamethasone (4 mg). The incidence of PONV, complete response rate (CR), severity of nausea and need for rescue antiemetics and analgesics were assessed at: 0-1 h, 1-6 h, 6-24 h and 24-48 h postoperatively. Results The mean (± SD) BMI was 35.0 (±5.2) kg m-2 for GI and 35.7 (±3.6) kg m-2 for GII. There was no significant difference between groups in PONV incidence, CR, severity of nausea, and need for rescue antiemetics or analgesics. The incidence of PONV for GI and GII was 15% and 27.5%, respectively, during the first 48 h (P = 0.17). Conclusions A body weight-adjusted dose of palonosetron was as effective as 75 μg for preventing PONV for 48 h in obese female patients who underwent breast surgery. Hence, the fixed dose may be preferable to the body weight-adjusted dose.